Definition of concepts of disability at the present stage development of the legislation of the Republic of Belarus - Novikova, Svyatlana I. (Journal of the Belarusian State University. Law, 2019)
The article considers theoretical, methodological and legal grounds for defining the concepts of disability. The author analyzes the conceptual approaches that reveal the paradigm of disability in the Republic of Belarus – from the economic to the medico-social one, which is the basis of the present-day state policy on disabled people and corresponds with UN basic documents on the rights of disabled people. Prospects of further development of the understanding of disability in the context of the biopsychosocial model are reviewed.
Keywords: models of disability; evolution of the concept of disability; attitude of the state to disabled people; rights of disabled people